Targeting Ca2+ signaling: A new arsenal against cancer. Issue 3 (March 2022) - Panda, Suman; Chatterjee, Oishika; Roy, Laboni; Chatterjee, Subhrangsu
Highlights: Drug resistance of cancer cells, which results in treatment failure, is a major concern in medical oncology. Ca 2+ plays an important role in acquired drug resistance by modulating gene expression in multidrug-resistant cancer cells. Calcium signaling intersects with many important hallmarks of cancer progression. Abnormal expression of Ca 2+ transporting channels and pumps is characteristic of several cancers. These channels and pumps are appropriate as specific drug targets for new cancer therapeutics. Abstract : The drug resistance of cancer cells is a major concern in medical oncology, resulting in the failure of chemotherapy. Ca 2+ plays a pivotal role in inducing multidrug resistance in cancer cells. Calcium signaling is a critical regulator of many cancer hallmarks, such as angiogenesis, invasiveness, and migration. In this review, we describe the involvement of Ca 2+ signaling and associated proteins in cancer progression and in the development of multidrug resistance in cancer cells. We also highlight the possibilities and challenges of targeting the Ca 2+ channels, transporters, and pumps involved in Ca 2+ signaling in cancer cells through structure-based drug design. This work will open a new therapeutic window to be used against cancer in upcoming years.